Simply guitar [video recording] - Mackay, Steve (Heatherton Victoria: Australia : Hinkler, 2013)
Have you wanted to play the guitar? Are you an absolute beginner who has never picked up an instrument or are you someone who can play but is looking to fill some gaps in your guitar or music in general, Simply Guitar has something for everyone. With Steve Mackay, an internationally acclaimed guitarist and professional guitar teacher, you will gain a deeper understanding of what you can do with guitar, how you can move forward with it as a creative and expressive tool and, most importantly, how to have fun with it!
Keywords: Guitar -- Instruction and study; Guitar -- Methods -- Self instructions